Patients' perceived involvement in vocationally oriented medical rehabilitation and its associations with satisfaction and motivation to deal with work-related issues during rehabilitation. (2015) - Lukasczik, Matthias; Gerlich, Christian; Neuderth, Silke
Little is known about the degree of involvement in treatment-related decision-making experienced by patients in work-related medical rehabilitative programs. It was investigated whether subgroups of patients in vocationally oriented medical rehabilitation (VOMR) can be distinguished regarding their degree of perceived participatory involvement and whether different degrees of perceived involvement during the consultation were associated with the motivation to deal with work-related problems and the satisfaction with treatment decision-making, the doctor-patient interaction and overall treatment. Data from a previous study including 283 orthopaedic rehabilitation patients were re-analysed. Latent class analysis yielded four types of perceived involvement (shared decision-making; patient-centred interaction with vs. without involvement in decision-making; no involvement). Higher involvement was associated with higher satisfaction, but not with the motivation to deal with work-related issues. Perceived involvement can be regarded as a helpful tool in promoting patient-centeredness in work-related medical rehabilitation. The lack of associations with motivation necessitates further research.